PENERAPAN MEDIA PEMBELAJARAN BERBASIS MACROMEDIA FLASH UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR SISWA PADA MATA PELAJARAN ALAT DAN MESIN PERTANIAN KELAS X ATP DI SMK NEGERI 7 MAJENE - Eka Putri; Husain Syam; Muhammad Rais (Jurnal Pendidikan Teknologi Pertanian, 2018)
This study is a classroom action research that aims to improve students' motivation and learning outcomes on the subjects of agricultural tools and agricultural machines class X agricultural  agribusiness  skills  program  (ATP)  SMK  Negeri  7 Majene  with the use of macromedia  flash based learning  media.  The subjects  of this study are the students  of class X ATP 2 SMK Negeri 7 Majene in the odd semester of academic  year 2017/2018 consisting  of 33 students. This research  was conducted  in two cycles consisting  of four activities, namely: planning, implementation, observation/observation,  and reflection. Data collection  of motivation  and learning  outcomes,  as well as activities  of student  learning activities is done by using observation  sheet and test result sheet in cycle I and cycle II. The collected  data is analyzed  quantitatively  and qualitatively.  Based  on the  results  of research, it can be concluded that the use of media based learning macromedia flash can improve  motivation  and  learning  outcomes  of  students  of class  X ATP  SMK  Negeri  7 Majene.